Ethics, Paediatric Doping and the Limitations of Gillick Consent - Michael McNamee (Ethics, Law and Society, 2017)
The issue of doping has generated considerable academic controversy since the 1980s. Perhaps a brave new world of medical enhancement is being ushered in with sport as its foil. There is always the danger, in supporting the banning of certain substances that one is considered timid (Bostrom 2005) or a weak-minded. Cassandra-like, figure. Worse, perhaps, for those who value academic freedom, one can be seen as an apologist for global institutions such as the International Olympic Committee (IOC) or the World Anti Doping Association (WADA). Another socio-psychological factor to be considered is whether Gillick consent to doping would be properly understood in relation to future addiction. This chapter presents a selective survey of relevant sports medical research to show that such doping is no mere fiction. The young Danish cyclists interviewed in this study do not seem to have been introduced to such contacts to procure drugs or gain the necessary advice about their use.